Perovskite / TOPCon laminated cell preparation method based on surface nanostructure modification

By performing nanostructure modification and micro-nano structure optimization on the silicon surface of perovskite/silicon dual-contact solar cells, combined with interface modification engineering, the problems of low photocurrent and poor epitaxial growth of nanocrystalline silicon in the prior art are solved, and the preparation of high-efficiency perovskite/TOPCon stacked solar cells is achieved.

CN119546142APending Publication Date: 2025-02-28QINGHAI HUANGHE HYDROPOWER DEV CO LTD XINING SOLAR POWER BRANCH +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411739947.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing perovskite/silicon dual-contact solar cells have problems such as low photocurrent, additional polishing process, and poor epitaxial growth of nanocrystalline silicon, which hinder their practical application.

Method used

Through surface nanostructure modification, metal-assisted chemical corrosion, plasma etching and self-assembly technology are used to accurately control the micro-nano structure of the silicon surface, design and optimize the micro-nano structure of dual-contact solar cells, and combine interface modification engineering to prepare high-quality perovskite films.

Benefits of technology

Perovskite/TOPCon stacked double junction solar cell with a photoelectric conversion efficiency of more than 32.5% is realized, which improves the overall efficiency, stability and reliability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite laminated solar cells, and provides a preparation method of a perovskite / TOPCon laminated double-junction solar cell. In order to solve the problems that in the prior art, surface textures are not matched with perovskite thin film preparation, the silicon surface passivation effect is poor and the like, the contradiction that the roughness of the upper surface textures of the TOPCon bottom cell is not matched with the precondition of perovskite crystallization film forming is balanced through methods of surface nanostructure modification, micro-nano structure design and optimization and the like; and the perovskite thin film is prepared by a solution method, so that the perfect matching of the micro-nano texture structure and the high-quality crystal perovskite thin film preparation process is realized. The perovskite / TOPCon laminated double-junction solar cell with the photoelectric conversion efficiency larger than 32.5% is prepared, and the photoelectric conversion efficiency, stability and reliability of the cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of perovskite tandem solar cells, and in particular to a method for preparing a perovskite / TOPCon tandem double-junction solar cell. Background technology:

[0002] In today's energy field, solar energy as a clean energy source has attracted much attention, and the development of solar cell technology is of key significance to improving the utilization efficiency of solar energy. As a new type of solar cell technology, perovskite / TOPCon tandem cells have great potential in improving the efficiency of photoelectric conversion. Recent progress in perovskite / silicon double-contact solar cells has shown that its best certified efficiency has reached 31.3%, which is higher than the Ogryn limit of silicon. This also provides another low-cost strategy to break through the Shockley-Queisser limit of single-contact solar cells, which is about 33.7%. But so far, most monolithic perovskite / silicon double-contact cells use a front-end polished silicon surface to accommodate solution-processed perovskite films. However, this planar configuration has the problem of low photocurrent and requires an additional polishing process, which hinders its practical application. Therefore, it is urgent to develop a high-efficiency perovskite / TOPCon tandem solar cell preparation process and scheme.

[0003] To date, surface passivated black silicon is often used as an ideal bottom cell for dual-contact cells because nanostructured black silicon can provide advanced light management. Double-contact perovskite solar cells are prepared by deposition or spin coating of perovskites on the bottom cell. The current preparation methods have the following problems: 1) The currently commonly used hydrogenated amorphous silicon (a-Si:H) has limited passivation effect on the black silicon surface because it causes poor nanocrystalline silicon epitaxial growth; 2) The matching problem of surface texture and perovskite film preparation needs to be solved, and the appropriate micro / nanostructure solar cell surface needs to be selected to fully utilize the incident light and achieve high conversion efficiency; 3) The engineering steps for manufacturing high-quality perovskite films are relatively complicated, and periodic nanostructures usually require complex manufacturing processes, which hinders their application in large-scale production industries.

[0004] The present invention provides a high-efficiency perovskite / TOPCon stacked solar cell preparation process and scheme, clarifies the process route for reconstructing the surface nanostructure of the TOPCon bottom cell substrate, and quantifies the passivation benefits of its surface defect states and the gains for improving the overall efficiency of the cell. The contradiction between the roughness of the surface texture of the "double-textured" TOPCon bottom cell and the preconditions for the crystallization of the perovskite film is balanced, and the micro-nano texture structure of the upper surface is designed to achieve a perfect match between the micro-nano texture structure and the high-quality crystalline perovskite film preparation process. The interface modification project is comprehensively utilized to solve the problems of the mismatch between the surface texture and the preparation of the perovskite film and the poor passivation effect of the silicon surface in the prior art, and a perovskite / TOPCon stacked double-junction solar cell with a photoelectric conversion efficiency greater than 32.5% is prepared. Summary of the invention:

[0005] In view of the shortcomings of the prior art or the need for improvement, the present invention aims to provide an efficient perovskite / TOPCon stacked cell preparation process to solve the problems in the prior art such as the mismatch between the surface texture and the perovskite film preparation and the poor passivation effect of the silicon surface, thereby improving the photoelectric conversion efficiency, stability and reliability of the cell.

[0006] The present invention provides a method for preparing an efficient perovskite / TOPCon stacked cell to overcome the deficiencies of the prior art. To achieve the above-mentioned purpose, the present invention adopts the following technical solutions:

[0007] Through surface nanostructure modification, precise control and reconstruction of silicon surface micro-nanostructures can be achieved, thereby improving the optical and electrical properties of the silicon surface and enhancing light capture capabilities. Design and optimize micro-nanostructures suitable for double-contact solar cells to maximize light absorption and photoelectric conversion efficiency. By testing parameters such as charge transfer rate and interface recombination rate under different material combinations and interface structures, the best material selection and interface engineering scheme are determined to improve the photoelectric performance and stability of the interface. The specific preparation method includes the following steps:

[0008] (1) New surface nanostructure modification: Use metal assisted chemical etching (MACE), plasma etching, self-assembly technology and other methods to modify the nanostructure of TOPCon silicon surface. The specific steps are as follows:

[0009] S1, prepare the etching solution: add different metal catalysts, such as silver, copper, etc., to the etching solution. Taking silver as an example, a hydrofluoric acid solution containing a certain concentration of silver nitrate needs to be prepared. The concentration of silver nitrate can be adjusted within the range of 0.01mol / L-0.1mol / L. The concentration of hydrofluoric acid also needs to be determined according to the specific experimental requirements, generally within a certain ratio range.

[0010] S2, silicon wafer treatment: immerse the cleaned silicon wafer in the prepared etching solution. Before immersion, the silicon wafer needs to undergo strict cleaning steps, such as ultrasonic cleaning with acetone, ethanol, and deionized water in sequence, to remove oil and impurities on the surface and ensure the uniformity of the corrosion reaction.

[0011] S3, control the temperature of the etching solution and the reaction time. Different combinations of temperature and time will affect the morphology and size of the nanostructure on the silicon surface.

[0012] S4, after the reaction is completed, the silicon wafer is rinsed with a large amount of deionized water to remove the residual etching solution, and then dried in a nitrogen atmosphere to prevent oxidation of the silicon wafer surface.

[0013] S5, plasma etching preparation, placing the cleaned silicon wafer into the reaction chamber of the plasma etching equipment, and ensuring the normal operation of the equipment's vacuum system, gas supply system, etc.

[0014] S6, gas selection and flow control, precisely control the gas flow, and determine the best gas flow combination according to the required etching depth and structural accuracy.

[0015] S7, solution preparation self-assembly solution, prepare a self-assembly solution containing specific organic molecules or nanoparticles (gold nanoparticles, silica nanoparticles, etc.). Organic molecules can be selected according to the characteristics of the desired nanostructure, such as organic molecules containing specific functional groups (such as amino groups, carboxyl groups, etc.). The concentration of the solution needs to be precisely controlled.

[0016] S8, soaking the silicon wafer, soaking the cleaned silicon wafer in a self-assembly solution, so that the nanoparticles self-assemble on the silicon surface to form a nanostructure.

[0017] (2) Micro-nanostructure design and optimization: Determine the possible direction of the micro-nanostructure based on the perovskite film preparation process requirements.

[0018] S1, preparation of micro-nano structures with different morphologies: preparation of micro-nano structure samples with different morphologies (such as columnar, spherical, pyramidal, etc.) by methods such as metal assisted chemical etching (MACE), plasma etching, and self-assembly technology.

[0019] S2, based on the determined optimal morphology, micro-nanostructure samples of different sizes are prepared by adjusting the process parameters.

[0020] S3, conduct photoelectric performance tests on the prepared micro-nanostructure samples of different sizes, and determine the optimal size parameters of the micro-nanostructure based on the test results to maximize the improvement of photocurrent density and optimize the light absorption and photoelectric conversion efficiency of solar cells.

[0021] S4, adjusting the layout and spacing of the micro-nano structure, by changing the relevant parameters in the preparation process to adjust the layout and spacing of the micro-nano structure, so as to achieve the optimization of the density of the micro-nano structure.

[0022] (4) Solution method for preparing perovskite thin films: The perovskite thin film process includes deposition of a framework layer, preparation of an organic salt layer (including solvent selection, reaction source treatment, use of additives, etc.), annealing, and optional passivation and encapsulation.

[0023] S1, raw material preparation, accurately weigh the perovskite precursor material, and accurately calculate the amount of each raw material according to the stoichiometric ratio based on the chemical composition of the target perovskite film and the required preparation amount.

[0024] S2, fixing the processed substrate on a spin coater, and using the spin coater to deposit a frame layer and a passivation layer.

[0025] S3, placing the substrate spin-coated with the perovskite precursor solution into an annealing device, and the annealing temperature needs to be precisely controlled according to the composition and crystallization requirements of the perovskite material. An inert gas atmosphere such as nitrogen and argon is maintained in the annealing device to prevent the perovskite film from oxidizing at high temperatures.

[0026] S4, dissolving the passivating agent in a suitable solvent to prepare a solution of appropriate concentration, and coating the solution on the surface of the perovskite film by spin coating or dipping.

[0027] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention should still be covered by the claims of the present invention. Other features of the present application will become easy to understand through the following description. Description of the drawings:

[0028] Figure 1 The figure is a flow chart of the preparation of the perovskite / TOPCon stacked double-junction solar cell described in the present invention;

[0029] Figure 2 A schematic diagram of the process of metal-assisted chemical etching of silicon nanostructures in the present invention;

[0030] Figure 3 Schematic diagram of the silicon surface plasma etching process described in the present invention;

[0031] Figure 4 is a schematic structural diagram of the stacked solar cell described in the present invention;

[0032] The numbers in the figure are: 1. Silicon substrate; 2. Nanoporous structure on silicon surface obtained by metal-assisted chemical etching (MACE) and ion beam etching; 3. Self-assembled nanostructure; 4. Perovskite film; 5. Perovskite crystal film. 6. Metal particles; 7. Silicon nanopores; 8. Silicon oxide layer during etching; 9. Photoresist; 10. Etching ions; 11. Etching area; 12. Nanostructure layer; 13. Nanoporous structure; 14. Self-assembled nanostructure layer; 15. Framework layer; 16. Passivation layer; 17. Perovskite crystal film layer. Specific implementation method:

[0033] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Given the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.

[0034] Example 1

[0035] The development of a new surface nanostructure modification method specifically includes the following steps:

[0036] The new surface nanostructure modification uses metal-assisted chemical etching (MACE), plasma etching, self-assembly technology and other methods to precisely control process parameters (such as silver nitrate concentration, temperature, and time in MACE, gas flow, power, and time in plasma etching, solution concentration and immersion time in self-assembly technology), to prepare and optimize nanostructures of various morphologies, sizes, and densities, so as to achieve precise control and reconstruction of the micro-nano structure on the silicon surface and improve its performance in perovskite / TOPCon stacked cells.

[0037] (1) Metal assisted chemical corrosion:

[0038] Furthermore, in a fume hood, silver nitrate powder was accurately weighed using a high-precision analytical balance, and the weighed silver nitrate was slowly added to an appropriate amount of hydrofluoric acid solution, while continuously stirring with a magnetic stirrer to fully dissolve the silver nitrate, thereby preparing a corrosion solution with a silver nitrate concentration of 0.03 mol / L.

[0039] Specifically, when the silver nitrate concentration is 0.03 mol / L, the nanostructures obtained are relatively uniform in size, reasonably distributed, and have regular nanopores. When the reaction temperature is 30°C, the growth rate of the nanostructure is moderate, and the obtained nanostructures perform well in depth and uniformity. When the reaction time is 30 minutes, the coverage and uniformity of the nanostructures reach a good level, and there will be no excessive growth of the nanostructures, interconnection and agglomeration, which will affect the surface quality.

[0040] Further, the silicon wafer is treated and reacted, and the cleaned silicon wafer (the cleaning process is ultrasonic cleaning with acetone, ethanol, and deionized water in sequence, the ultrasonic frequency is 40kHz, each ultrasonic time is 15 minutes, and then it is blown dry with high-purity nitrogen) is carefully immersed in the prepared etching solution.

[0041] Furthermore, the reaction container was placed in a constant temperature water bath, maintained at 20°C, and the reaction time was 20 minutes. During the reaction, the silver ions in the solution catalyzed the reaction on the silicon surface, causing the silicon atoms to react chemically with the hydrofluoric acid, thereby forming silicon nanopores 7 on the silicon surface.

[0042] Furthermore, after the reaction is completed, the silicon wafer is immediately rinsed with a large amount of deionized water to completely remove the residual corrosive liquid, and then the silicon wafer is placed in a nitrogen purge device and dried under a nitrogen atmosphere to prevent oxidation of the silicon wafer surface.

[0043] (2) Plasma etching:

[0044] Furthermore, the cleaned silicon wafer is placed in a reaction chamber of a plasma etching device to ensure that the chamber is well sealed. A mixed gas of fluorine (F2) and nitrogen trifluoride (NF3) is selected as the etching gas.

[0045] Specifically, the gas flow controller is used to precisely adjust the F2 flow rate to 30sccm and the NF3 flow rate to 50sccm to control the etching rate and etching effect. At this time, the etching rate is slow, but the size of the obtained micro-nano structure is small and the surface is smooth; as the gas flow rate increases, the etching rate increases, the size of the micro-nano structure increases, but the surface roughness also increases, and the uniformity of the structure is affected to a certain extent.

[0046] Furthermore, the process parameters of the plasma etching equipment are set, and the plasma power is set to 200 W. Under this power, the plasma energy is moderate, the etching rate is fast, and it will not cause damage to the surface of the silicon wafer, or defects such as microcracks. Plasma 10 is generated using a radio frequency power supply.

[0047] Specifically, the pressure of the reaction chamber is maintained at 5 Pa by a vacuum pump and a pressure controller to ensure that the gas molecules have a suitable collision and reaction probability in the chamber. The etching time is set to 15 minutes. During the etching process, the active ions in the plasma react chemically with the silicon surface atoms to remove the silicon atoms, thereby forming a micro-nano structure 2. After the etching is completed, wait for the gas in the chamber to be discharged, and then take out the silicon wafer for subsequent processing.

[0048] (3) Self-assembly technology

[0049] Furthermore, powder containing specific organic molecules (such as an organosilane coupling agent containing amino groups) is accurately weighed and dissolved in a suitable amount of solvent (such as ethanol) to prepare a self-assembly solution.

[0050] Specifically, a magnetic stirrer is used to stir for several hours until the solution is completely dissolved, and a solution with a concentration of 0.3 mg / mL is prepared. At this solution concentration, the number and distribution of the self-assembled nanostructures are relatively uniform, and the structural stability is good.

[0051] Further, the cleaned silicon wafer is immersed in the solution, and the immersion container needs to be well sealed to prevent the solvent from volatilizing. The immersion time is 5 hours, during which the organic molecules self-assemble on the silicon surface through intermolecular forces (such as hydrogen bonds, van der Waals forces, etc.) to form nanostructures 3.

[0052] Furthermore, after the immersion is completed, the silicon wafer is taken out of the solution and the surface solution is gently blown dry with nitrogen. The silicon wafer is then placed in an oven set at 120° C. for annealing for 30 minutes. During the heating process, the chemical bonding between the organic molecules and the silicon surface is enhanced, and possible residual solvent molecules are removed, so that the self-assembled nanostructure layer 14 is more stably attached to the silicon surface.

[0053] Example 2

[0054] The perovskite solution method is used to prepare the perovskite film 4 on the nanostructured silicon substrate 1, which specifically includes the following steps:

[0055] (1) Solution preparation and pretreatment

[0056] Further, raw material preparation and dissolution are performed. Perovskite precursor materials, methylammonium iodide (MAI) and lead iodide (PbI2) are accurately weighed, and a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) is used.

[0057] Specifically, the methylamine lead iodide (MAPbI3) precursor, in which the purity of methylammonium iodide (MAI) and lead iodide (PbI2) is more than 99.9%. MAI and PbI2 are slowly added to a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a stoichiometric ratio of 1:1, and the volume ratio of the mixed solvent is 1:2. Use a magnetic stirrer to stir the solution at room temperature, the stirring speed is 500rpm, and the stirring time is continuous for 5 hours to ensure that the precursor is fully dissolved to form a uniform and stable solution.

[0058] Further, additives are added and filtered. An appropriate amount of ammonium iodide (NH4I) is added to the above solution as an additive, and the amount of NH4I added is 1% of the total mass of the precursor. Continue to stir the solution for 2 hours to evenly disperse the additive in the solution. The solution is then filtered through a 0.22μm filter membrane. The filtration process is carried out in an inert gas-protected glove box to prevent the solution from contacting moisture and oxygen in the air, ensuring the purity of the solution, and obtaining a clear, transparent and impurity-free perovskite precursor solution with a solution concentration of 1mol / L.

[0059] (2) Thin film deposition and annealing

[0060] Furthermore, the TOPCon bottom cell with optimized interface passivation layer was placed on the sample stage of the spin coater, and the bottom cell was fixed using a vacuum adsorption device to ensure that it would not move during the spin coating process.

[0061] Specifically, 0.5 mL of the perovskite precursor solution was slowly dripped onto the center of the bottom battery surface through a microsyringe, and the dripping speed was controlled at 0.1 mL / s. The parameters of the spin coater were set, and the spin coater was first rotated at a low speed of 500 rpm for 5 seconds to evenly spread the solution on the bottom battery surface, and then quickly accelerated to 3000 rpm for 30 seconds. Under the action of centrifugal force, the solvent in the solution began to evaporate, and the perovskite precursor formed a uniform perovskite film 4 on the bottom battery surface.

[0062] Furthermore, an annealing treatment is performed to promote the growth of the perovskite crystal by precisely controlling the annealing temperature and time, thereby improving the crystallinity and quality of the perovskite crystal thin film layer 18 .

Claims

1. A method for preparing a perovskite / TOPCon stacked double-junction solar cell, characterized in that: The following steps are involved: (1) Novel surface nanostructure modification: According to the requirements of the perovskite film preparation process, the micro-nano structure is determined, and the TOPCon silicon surface is nanostructured by comprehensively utilizing metal-assisted chemical etching (MACE), plasma etching, and self-assembly technology. The specific operations are as follows: S1, preparation of samples with different morphologies: preparation of micro-nanostructure samples with different morphologies (such as columnar, spherical, pyramidal, etc.) by metal-assisted chemical etching (MACE), plasma etching, self-assembly technology and other methods; S2, size optimization: Based on the determined optimal morphology, micro-nanostructure samples of different sizes are prepared by adjusting the process parameters, and the photoelectric performance is tested. The optimal size parameters of the micro-nanostructure are determined based on the test results; S3, density optimization: adjust the layout and spacing of micro-nano structures by changing the relevant parameters in the preparation process to achieve density optimization. S4, preparing a corrosive solution: adding a metal catalyst, silver nitrate, to a hydrofluoric acid solution, wherein the concentration of the silver nitrate is adjusted within a range of 0.01 mol / L to 0.1 mol / L, to prepare a corrosive solution; S5, silicon wafer treatment: immerse the silicon wafer after strict cleaning (using acetone, ethanol, and deionized water ultrasonic cleaning in sequence, ultrasonic frequency 40kHz, each ultrasonic cleaning time 15 minutes, and then blow-dried with high-purity nitrogen) in the etching solution; S6, controlled corrosion conditions: corrosion liquid temperature 30 ° C, reaction time 30 minutes; S7, post-treatment: After the reaction is completed, the silicon wafer is rinsed with a large amount of deionized water to remove the residual etching solution, and then dried under a nitrogen atmosphere; S8, preparation: placing the cleaned silicon wafer into the reaction chamber of the plasma etching equipment to ensure the normal operation of the equipment-related systems; S9, gas control: select a mixed gas of fluorine (F2) and nitrogen trifluoride (NF3) as the etching gas, and accurately control the F2 flow rate at 30 sccm and the NF3 flow rate at 50 sccm; S10, setting parameters: setting the plasma power to 200 W, the reaction chamber pressure to 5 Pa, and the etching time to between 10 and 20 minutes; S11, solution preparation: preparing a self-assembly solution containing specific organic molecules (containing functional groups such as amino or carboxyl groups) or nanoparticles (such as gold nanoparticles and silica nanoparticles), with a solution concentration of 0.3 mg / mL; S12, silicon wafer soaking: soak the cleaned silicon wafer in the self-assembly solution for 5 hours. After soaking, dry the surface solution with nitrogen gas, and then anneal in an oven at 120° C. for 30 minutes. (2) Preparation of perovskite film by solution method, including deposition of framework layer, preparation of organic salt layer, annealing and optional passivation and encapsulation, the specific steps are as follows: S1, solution preparation and pretreatment raw material preparation: accurately weigh the perovskite precursor material, and accurately calculate the amount of each raw material according to the stoichiometric ratio based on the chemical composition of the target perovskite film and the required preparation amount; S2, dissolving and filtering: dissolving the precursor in a suitable organic solvent, adding an appropriate amount of additives, stirring, and filtering to obtain a clear and stable perovskite precursor solution with a solution concentration of 1-2 mol / L; S3, thin film deposition and annealing treatment: Deposition operation: fix the treated substrate on the spin coater, take 0.5mL of perovskite precursor solution and slowly drip it on the center of the substrate, first spin at a low speed of 500rpm for 5 seconds, then accelerate to 3000rpm and spin for 30 seconds; S4, annealing treatment: after the spin coating is completed, the sample is immediately placed in an annealing device, the annealing temperature is between 80-120°C, the annealing time is between 30 minutes, and the annealing device is maintained with an inert gas atmosphere such as nitrogen or argon; S5, passivation treatment: dissolve the passivator in a suitable solvent to prepare a solution with a concentration of 0.01wt%-0.5wt%, and apply it on the surface of the perovskite film by spin coating or dipping. The spin coating speed is 1000-3000rpm, and the dipping time is 1-10 minutes. After treatment, anneal at 80-120°C for 10-30 minutes.

2. The preparation method according to claim 1, wherein in metal assisted chemical etching (MACE), when the silver nitrate concentration is 0.03 mol / L, the reaction temperature is 30° C., and the reaction time is 30 minutes, the formed nanostructure has uniform size, reasonable distribution and regular nanopore shape.

3. The preparation method according to claim 1, wherein in plasma etching, when the F2 flow rate is 30 sccm, the NF3 flow rate is 50 sccm, the plasma power is 200 W, the reaction chamber pressure is 5 Pa, and the etching time is 15 minutes, a micro-nano structure with a smaller size and a smoother surface can be obtained, and as the gas flow rate increases, the etching rate increases, the size of the micro-nano structure increases but the surface roughness increases.

4. The preparation method according to claim 1, wherein in the self-assembly technology, when the solution concentration is 0.3 mg / mL and the immersion time is 5 hours, the number and distribution of the nanostructures formed by self-assembly are uniform and the structural stability is good.

5. The preparation method according to claim 1, wherein when the perovskite film is prepared by a solution method, the amount of the additive added to the perovskite precursor solution is 1% of the total mass of the precursor, and the solvent is a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and the volume ratio is 1:1-1:

3.

6. The preparation method according to claim 1, wherein during the deposition of the perovskite film, when the spin coating speed is 3000 rpm and the spin coating time is 30 seconds, a perovskite film with moderate thickness and good photoelectric performance can be obtained.

7. A perovskite / TOPCon stacked double-junction solar cell, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6. illustrate During the specific implementation process, the range and conditions of various process parameters are determined through research and experiments, aiming to achieve the preparation of efficient and stable perovskite / TOPCon stacked double-junction solar cells, improve the photoelectric conversion efficiency, stability and reliability of the cells, and at the same time solve the problems existing in the existing technology, such as the mismatch between the surface texture and the preparation of the perovskite film, and the poor passivation effect of the silicon surface. These claims are intended to protect the unique technical solutions and innovations of the invention in the field of perovskite / TOPCon tandem battery preparation.